Process intensification through microreactor application - Pohar, A. (Array, 2009)
Summary: A substantial amount of publications each year demonstrate how through the application of microprocess engineering significant benefits can be obtained concerning product yield, purity and time needed for chemical transformations, compared to the equivalent bulk reactions. Microreactors clearly hold the potential to revolutionize chemical synthesis, but scarce articles demonstrate specific suggestions for possible replacement of existent industrial processes. The focus of this review is to assess whether significant advances have been made for the implementation of microstructured devices into existent industrial processes or their complete replacement. The papers are reviewed in light of particular beneficial microreactor characteristics with potential for process intensification